Growth Arrest-Specific Protein 6 Protects Against Renal Ischemia-Reperfusion Injury - Giangola, Matthew D. (J Surg Res, 2015)
BACKGROUND: Renal injury caused by ischemia-reperfusion (I/R) often occurs following shock or transplantation. Growth arrest-specific protein 6 (Gas6) is a secreted protein that binds to the TAM-family tyrosine kinase receptors which modulate the inflammatory response and activate cell survival pathways. We hypothesized that Gas6 could have a protective role in attenuating the severity of renal injury after I/R. MATERIALS AND METHODS: Adult mice were subjected to 45 min of bilateral renal ischemia. Recombinant mouse Gas6 (rmGas6, 5 μg/mouse) or normal saline (vehicle) was administered intraperitoneally 1 h before ischemia and all subjects were sacrificed at 23 h after I/R for blood and tissue analysis. The expression of protein and mRNA was assessed by Western blotting and qPCR, respectively. RESULTS: Treatment with rmGas6 significantly decreased serum levels of creatinine and BUN by 29% and 27%, respectively, improved the renal histological injury index and reduced the apoptosis in the kidneys, compared to the vehicle. Renal mRNA levels of IL-1β, IL-6, TNF-α, KC and MIP-2 were decreased significantly by 99%, 60%, 53%, 58%, and 43%, with rmGas6 treatment, respectively. After I/R, renal IκB-α levels were reduced by 40%, while they returned to sham levels with rmGas6 treatment. The mRNA levels of iNOS and COX-2 were reduced by 79% and 70%, respectively, while the expression of cyclin D1 was increased by 2.1-fold in the rmGas6-treated group, compared to the vehicle. CONCLUSIONS: Gas6 suppresses the NF-κB pathway and promotes cell proliferation, leading to reduction of inflammation and protection of renal injury induced by I/R.